To Regulate or to Liberate? Business Development and the Dilemmas of the Authorities Regarding the Shape of Economic Policy in the Years 1989–1995 - Kamosiński, Sławomir (Studia Historiae Oeconomicae, 2017)
In the history of Poland, it is very clear that the year 1989 is one of the most distinctive turning points - a final break with the political, social, and economic system built in the period of the Polish People’s Republic, and reinstatement of democracy and free market economy upon the will of the nation. The world had never witnessed a transformation process as large as the one that occurred in Poland after the year 1989. Importantly, this transformation could not be programmed. Therefore, economic policy implemented by governments of the time was constantly amended as problems arose. The course of ownership transformation was monitored. It was observed that the so-called Privatization Act of July 13, 1990 lacked regulations concerning environment protection. Freedom to establish truck transport companies resulted with many anomalies, as it enabled, for instance, the use of trucks in poor technical condition. New regulations in insurance law, which lifted mandatory insurance of production assets against damage from natural disasters, meant that many entrepreneurs decided not to have this insurance. Such was the shape of the economic reality in the first years of the transition, between 1989 and 1995. The state did not want to regulate all aspects of economic life. However, as time went by, politicians and MPs received information from the free market, indicating a need for solutions regulating some sectors of the economy. This article discusses the three aspects of economic life mentioned above, and points out how the governmental and parliamentary strategies towards these aspects of economic life changed in the first years of transformation (1989-1995).